2020
DOI: 10.1021/acs.jpcb.0c07286
|View full text |Cite
|
Sign up to set email alerts
|

Direct Visualization of the Binding of Transforming Growth Factor Beta 1 with Cartilage Oligomeric Matrix Protein via High-Resolution Atomic Force Microscopy

Abstract: This work reports the first direct observations of binding and complex formation between transforming growth factor beta 1 (TGF-β1) and cartilage oligomeric matrix protein (COMP) using high-resolution atomic force microscopy (AFM). Each COMP molecule consists of pentamers whose five identical monomeric units bundle at N-termini. From this central point, the five monomers' flexible arms extend outward with C-terminal domains at the distal ends, forming a bouquet-like structure. In commonly used buffer solutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Further, TGF-β is a well-documented factor that drives anti-PD-L1 resistance in colon cancer ( 46 ). Many studies reported TGF-β to be co-expressed with COMP ( 4 , 47 , 48 ), which could lead to immunosuppression even under microsatellite instability. In contrast, COMP expression by cancer cells was not correlated with MSI.…”
Section: Discussionmentioning
confidence: 99%
“…Further, TGF-β is a well-documented factor that drives anti-PD-L1 resistance in colon cancer ( 46 ). Many studies reported TGF-β to be co-expressed with COMP ( 4 , 47 , 48 ), which could lead to immunosuppression even under microsatellite instability. In contrast, COMP expression by cancer cells was not correlated with MSI.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the authors observed binding between the transforming growth factor beta 1 (TGF-β1) and cartilage oligomeric matrix protein (COMP). 51 TGF-1/COMP complexes contained one to three COMP and multiple TGF-1 dimers (Fig. 4C), indicating that multivalent binding exists.…”
Section: Topographical Imaging Of Protein-drug Interactionmentioning
confidence: 98%
“…Cartilage oligomeric matrix protein (COMP), namely thrombospondin-5 (TSP-5), interacts with type I and type II collagen to regulate the assembly and stabilization of the extracellular matrix [ 9 , 10 ]. With a pentameric structure composed of five identical monomers, COMP can simultaneously interact with multiple TGF-β1 molecules, contributing to the high efficacy in the sustained activation of the TGF-β signaling pathway [ 11 ]. Moreover, COMP is significantly upregulated in CRCs and is co-expressed with key EMT genes and associated with poor survival [ 10 ].…”
Section: Introductionmentioning
confidence: 99%